The Impact of the International Livestock Research Institute 2020
DOI: 10.1079/9781789241853.0639
|View full text |Cite
|
Sign up to set email alerts
|

Economics and policy research at ILRI, 1975-2018.

Abstract: This chapter looks at the livestock policy and economics research at the International Livestock Research Institute (ILRI) and its predecessor, the International Livestock Centre for Africa (ILCA), which have focused on the following problems: (i) the historical problem of supply response; (ii) animal health services and productivity; (iii) responding to the 'Livestock Revolution'; (iv) policy and technical barriers to smallholder dairying; (v) livestock and poverty; (vi) markets, institutions and competitiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…However, regional average cattle prices in Somalia grew at a high average monthly rate of 1.25%, and as expected the estimate of this variable is positive, although the elasticity is relatively low at 5.2%. Still, this suggests some pressure on regional demand, which is important given that many Ethiopian cattle from the agro‐pastoralist lowlands end up in markets in Saudi Arabia and the Middle East (Jabbar et al., 2007).…”
Section: Hedonic Regression Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, regional average cattle prices in Somalia grew at a high average monthly rate of 1.25%, and as expected the estimate of this variable is positive, although the elasticity is relatively low at 5.2%. Still, this suggests some pressure on regional demand, which is important given that many Ethiopian cattle from the agro‐pastoralist lowlands end up in markets in Saudi Arabia and the Middle East (Jabbar et al., 2007).…”
Section: Hedonic Regression Resultsmentioning
confidence: 99%
“…Table 4 reports estimates from regressions that split the sample by highland markets (where mixed crop‐livestock farming predominates and farmers mostly own one to two cattle primarily for a variety of functions including traction) and lowland markets (where agro‐pastoralism predominates, with large herds specialized for beef production). Unsurprisingly—given the extensive structural differences of these agro‐ecologies and different marketing channels (Jabbar et al., 2007)—there are a number of sizable and statistically significant differences across the two sets of markets.…”
Section: Hedonic Regression Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For some developing countries, ensuring food safety for the masses would involve a flexible retail modernization approach that does not focus on supermarkets alone (Wertheim-Heck, Vellema, & Spaargaren, 2015). Early work showed that informal milk markets created more employment per unit of product than did formal markets in Kenya, Bangladesh, and Ghana, and has been the bases for the longstanding involvement of CGIAR researchers in dairy sector reforms in Kenya (Jabbar et al, 2020).…”
Section: Markets and Value Chainsmentioning
confidence: 99%